2016
DOI: 10.1007/s00383-016-4038-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding functional variations in the Hirschsprung disease spectrum (variant Hirschsprung disease)

Abstract: Hirschsprung disease (HSCR) is a fairly well understood congenital, genetically based functional obstruction due to the congenital absence of ganglion cells in the distal bowel. However, although over 90% of Hirschsprung cases conform to the normally accepted histological diagnostic criteria, it has become increasingly clear that in addition to HSCR, there is a group of functional disturbances relating to a number of other congenital neurodysplastic conditions causing some degree of gastrointestinal tract malf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 103 publications
0
10
0
6
Order By: Relevance
“…The resulting ENS is a complex interconnected network containing~500 million neurons in humans; more than the spinal cord (24,26). Gut motility disorders can arise from the loss of subtypes of enteric neurons as occurs in some forms of diabetic gastroparesis, achalasia, and Chagas disease (28,42,50,58) or the congenital absence of the ENS, which occurs in Hirschsprung disease (6,12,31,44,49,54). GI motility disorders caused by enteric neuropathies are some of the most clinically challenging GI conditions to manage (18 -20, 42) and thus there has been considerable interest in the potential of cell therapy to treat such disorders (9,11,28).…”
mentioning
confidence: 99%
“…The resulting ENS is a complex interconnected network containing~500 million neurons in humans; more than the spinal cord (24,26). Gut motility disorders can arise from the loss of subtypes of enteric neurons as occurs in some forms of diabetic gastroparesis, achalasia, and Chagas disease (28,42,50,58) or the congenital absence of the ENS, which occurs in Hirschsprung disease (6,12,31,44,49,54). GI motility disorders caused by enteric neuropathies are some of the most clinically challenging GI conditions to manage (18 -20, 42) and thus there has been considerable interest in the potential of cell therapy to treat such disorders (9,11,28).…”
mentioning
confidence: 99%
“… 19 , 20 Regarding one of the previously reported cases, 6 Moore suggested that the isolated deficiency of myenteric ganglion cells seen therein could represent a secondary mechanism or apoptosis of the ganglia due to an immune reaction. 4 We suggest that myenteric ganglion cells that had already migrated were eliminated by an eosinophil-mediated mechanism in these three cases.…”
Section: Discussionmentioning
confidence: 73%
“…HD is defined as a functional intestinal obstruction due to the congenital absence of ganglion cells in both Meissner and Auerbach plexuses in the distal colon. 4 , 10 As is common in HD, the distal edges of myenteric and submucosal ganglion cells are aligned. 4 However, Kapur reported that the distal edge of submucosal ganglion cells was significantly more proximal than the distal edge of myenteric ganglion cells in 19/59 cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hirschsprung disease (HD) is a congenital, genetically-based functional obstruction due to the congenital absence of ganglion cells in the distal bowel (aganglionosis) (1,2). The absence of ganglion cells along with an analysis of hypertrophy and hyperplasia of nerves in the nerve plexus of submucosa and muscularis mucosae in rectal biopsy specimens (RB) are regarded as potential hallmarks for its diagnosis (3).…”
mentioning
confidence: 99%